INDICATORS OF PHYSICAL DEVELOPMENT OF WOMEN IN THE FIRST PERIOD OF MATURE AGE HAVING DIFFERENT TYPES OF POSTURE - Samoiliuk, O. V.; Kashuba, V. O.; Grygus, I. M. (Rehabilitation and Recreation, 2025)
Introduction. Currently, in scientific publications devoted to various aspects of the physical development of mature individuals, there are more and more attention paid to the study of indicators somatometry and somatoscopy. The aim of the study was to determine the somatometric indicators of women aged 25–34 with different types of posture. Research methods: theoretical analysis and generalization of literary sources; anthropometry; photography and analysis of posture, pedagogical experiment, methods of mathematical statistics. Results. Based on the medical records of women aged 25–34, information about their posture types was obtained. It should be noted that women aged 30–34 had a higher average body weight compared to women aged 25–29, regardless of the posture type. Calculations indicated that the difference in body weight between age groups was minimal among women with normal posture, while women having a round-shouldered posture and scoliotic posture had a noticeable increase in body weight depending on the age. The average value of the ideal body weight index, calculated using the Beringard formula, was (61,11 ± 0,97) kg with individual variations within the range from 59,13 to 63 kg. That is, the actual body weight of women in the total sample did not differ much from the ideal body weight. It should be noted that body length did not differ significantly between age groups, but women having the round-shouldered posture within the age group of 25–29 years had the smallest average body length, and women of the same age with a scoliotic posture had the largest body length. It was worth noting that significant differences were found in body length, Quetelet index and Rohrer index between groups having different types of posture for women aged 25–29 years, namely, women having had the scoliotic posture had a larger body length, but smaller Quetelet and Rohrer indices compared to women that had a round-shouldered posture. Women aged 30–34 years had differences that were less pronounced or absent, which indicates a smaller influence of posture type on these indicators at an older age. In addition, according to data on the harmony of physical development (according to the Rohrer index), it was found that its value (from 12,3 standard units to 14,9 standard units) fluctuated within two levels (medium-harmonious development and above-medium level). The average value was 13,15 standard units with a standard deviation of 0,44 standard units. Only 11,1% of women had individual values exceeding the norm. The development of most of them (88,9%) was harmonious. Conclusions. It was found that depending on age, the body weight of women tended to increase, which may be associated with both metabolic changes and behavioral changes, such as decreased physical activity, transformation of eating habits, etc. The corresponding trend in the Quetelet index means that the probability of an increase in the risk of developing overweight or obesity increases with the age.